Respostas

2014-05-19T20:31:30-03:00
(-2/3)³ + 1 = ??

       2
³
( -   ----) + 1 =
       3
³

      8
(- -------) + 1 =     
     27

   -8   + 27                   19
-----------------  =          --------- =   19/27
         27                     27
1 1 1
2014-05-19T20:53:29-03:00
(\frac{-2}{3})^{3}
 (-2)^{3}  = - 8
 3^{3} = 27

Logo;
(\frac{-2}{3})^{3} =
 \frac{-8}{27}

Fazendo a operação :
 \frac{-8}{27} + 1 =  \frac{-8 + 27}{27}  = 19/27

Espero ter ajudado

1 5 1
Muito obrigado.
falha minha??? corrigido!!!